Effect of Augmented Reality Assisted Problem Based Learning on Students' Critical Thinking Skills - Agnia Nurhaliza; Uus Toharudin; Devi Rahmiati (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The critical thinking ability of third-grade elementary school students is still low, especially in analyzing problems and drawing logical conclusions, due to learning that has not encouraged active student involvement. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Augmented Reality media on the critical thinking ability of third-grade students at SDN Wangisagara 03. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The study population consisted of 56 students divided into an experimental class (28 students) and a control class (28 students). Data collection techniques were carried out through a critical thinking ability test in the form of 15 multiple-choice questions given at the pretest and posttest stages. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, and the Mann-Whitney hypothesis test with the help of IBM SPSS Statistics 27. The results showed that the critical thinking ability of students who participated in PBL learning assisted by Augmented Reality media was better than students in the control class. Thus, the PBL model supported by Augmented Reality media has a positive effect on the critical thinking ability of elementary school students.